High litter quality enhances plant energy channeling by soil macro‐detritivores and lowers their trophic position - Zhong, Linlin; Larsen, Thomas; Lu, Jing‐Zhong; Scheu, Stefan; Pollierer, Melanie M. (Ecology (Durham), 2025)
Detritus‐based resources, that is, plant litter, are a major energy source for many living organisms and are considered to be a key determinant of primary production and nutrient cycling. Earthworms are among the most important macro‐detritivores in terrestrial food webs and play a crucial role in facilitating these processes in terrestrial ecosystems. Yet, the influence of litter quality on earthworm nutrition, and consequently on soil food web dynamics, has remained largely underexplored, mainly for methodological reasons. Here, we combined bulk and compound‐specific stable isotope analysis of amino acids to investigate the dietary contribution of different quality litter resources to earthworm species of different ecological groups. Our findings show that earthworms acquired most essential amino acids from bacterial (~60%) and plant (~30%) resources, with the latter increasing in importance with higher litter quality, resulting in lower trophic positions across earthworm species. The high bacterial contribution to earthworms corresponds to the dominance of bacteria in the experimental soil, suggesting that bacteria served as an important intermediate link in transferring detritus‐based resources to earthworms. Bacterial contributions were notably higher in the soil‐feeding earthworm species than in the litter‐feeding earthworm species, likely due to more pronounced ingestion of soil by soil‐feeding earthworms. Overall, our study indicates that a major group of soil macro‐detritivores, earthworms, receive detrital resources via the bacterial energy channel. Further, it underscores the important role of litter quality in shaping the trophic niches of detritivores, thereby influencing the overall structure of soil food webs.